Listening to Music in the First, but not the Last 1.5 km of a 5-km Running Trial Alters Pacing Strategy and Improves Performance - Lima-Silva, A. E.; Silva-Cavalcante, M. D.; Pires, F. O.; Bertuzzi, R.; Oliveira, R.S. F.; Bishop, D. (International Journal of Sports Medicine, 2012)
We examined the effects of listening to music on attentional focus, rating of perceived exertion (RPE), pacing strategy and performance during a simulated 5-km running race. 15 participants performed 2 controlled trials to establish their best baseline time, followed by 2 counterbalanced experimental trials during which they listened to music during the first (Mstart) or the last (Mfinish) 1.5 km. The mean running velocity during the first 1.5 km was significantly higher in Mstart than in the fastest control condition (p<0.05), but there was no difference in velocity between conditions during the last 1.5 km (p>0.05). The faster first 1.5 m in Mstart was accompanied by a reduction in associative thoughts compared with the fastest control condition. There were no significant differences in RPE between conditions (p>0.05). These results suggest that listening to music at the beginning of a trial may draw the attentional focus away from internal sensations of fatigue to thoughts about the external environment. However, along with the reduction in associative thoughts and the increase in running velocity while listening to music, the RPE increased linearly and similarly under all conditions, suggesting that the change in velocity throughout the race may be to maintain the same rate of RPE increase.
Keywords: perceived exertion; attentional focus; fatigue; sports performance